2022
DOI: 10.1016/j.jhlste.2022.100369
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 pandemic trigger career anxiety in tourism students? Exploring the role of psychological resilience

Abstract: This study aims to determine how the COVID-19 pandemic affects career anxiety of tourism students, who are the potential future employees of tourism and hospitality industry. Data was collected using an online survey with 1097 undergraduate students in the field of tourism in Turkey. The results of the study revealed that perceived risk of infection and fear of COVID-19 significantly impact students' career anxiety, and fear of COVID-19 mediate the relationship between perceived infection risk and career anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 93 publications
(114 reference statements)
2
22
0
1
Order By: Relevance
“…This orientation also confirms the findings of a prior study in terms of young individuals who are realistic about the lack of a current work environment but seek some solutions such as networking and relocating (Parola & Felaco, 2020). Students' intention to adapt to changes by various means of career adaptability or resilience as an individual resource against challenges reduces anxiety and worries about their abilities, career, and employment environment (Boo et al, 2021;Üngüren & Kaçmaz, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This orientation also confirms the findings of a prior study in terms of young individuals who are realistic about the lack of a current work environment but seek some solutions such as networking and relocating (Parola & Felaco, 2020). Students' intention to adapt to changes by various means of career adaptability or resilience as an individual resource against challenges reduces anxiety and worries about their abilities, career, and employment environment (Boo et al, 2021;Üngüren & Kaçmaz, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This type of anxiety may originate from expected economic recessions in any employment environment (Cao et al, 2020;Tsai et al, 2017). Studies reveal the career anxiety of higher education students during the pandemic and their orientation for career adaptability (Boo et al, 2021) and resilience (Üngüren & Kaçmaz, 2022) to balance the effects of anxiety in their lives. In addition, during uncertain periods 10.48119/toleho.1200532 like COVID-19, students' orientation towards industry may be unstable.…”
Section: Student Anxiety During the Covid-19 Periodmentioning
confidence: 99%
“…According to these studies, the fear of being a victim of COVID-19 adversely impacted students' wellbeing and critical thinking abilities. In addition, the fear of COVID-19 increased students' anxiety levels which in turn decreased their performance ( 91 ).…”
Section: Discussionmentioning
confidence: 99%
“…An experience summarizing from containing the COVID-19 pandemic suggests that nurses should be encouraged to mediate acute stress via having a capacity of resilience during the pandemic, which adjusts resources to support ICU nurses to manage stress and promote wellbeing (Thusini, 2020 ), further maintaining calling. COR theory suggests that resilience is a significant protector under stressful conditions; the latest study confirmed that psychological resilience, which is an individual resource against difficulties, represents a factor that reduces career anxieties of students in the face of pandemic-related negative impacts (Üngüren and Kaçmaz, 2022 ). A new study found that the engagement in learning, clarity of professional identity, and social support can predict students' calling (Dalla Rosa et al, 2019 ).…”
Section: Theory and Hypothesesmentioning
confidence: 98%